Lifshitz holography with a probe Yang-Mills field - Schaposnik, Fidel Arturo (2013)
Taking as a probe an SU(2) gauge field with Yang-Mills action in a 3 + 1 dimensional Lifshitz black hole background, we use the gauge/gravity correspondence to discuss finite temperature effects in the dual theory defined on the boundary. In order to test the dependence of results on the anisotropic scaling exponent z we consider two analytical black hole solutions with z=2 and z=4. Apart from solving the equations of motion in the bulk using a numerical approach, we also apply an analytical approximation allowing the determination of the phase transition character, the critical exponent and the critical temperature behavior as a function of z.